Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Enhanced conversion efficiency in dye-sensitized solar cells based on hydrothermally synthesized TiO2-MWCNT nanocomposites - Muduli, Subas; Lee, Wonjoo; Dhas, Vivek V.; Mujawar, Sarfraj; Dubey, Megha; Vijayamohanan, K.; Han, Sung-Hwan; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2009)
A 50 % enhancement in the conversion efficiency (4.9-7.37 %) is realized in dye-sensitized solar cells Using hydrothermally synthesized TiO2-multiwalled carbon nanotube (MWCNT) nanocomposites as compared to hydrothermally synthesized TiO2 without MWCNT and Degussa P25. Several characterizations have been employed to reveal the nature of the modification imparted to the MWCNTs under hydrothermal processing conditions and the resulting TiO2-MWCNT conjugation through -COOH groups. Efficient charge transfer In the nanocomposite and efficient electron transport by MWCNT (significantly higher Incident-photon-to-current conversion efficiency) are suggested to be the possible reasons for the enhancement.
Keywords: Carbon nanotubes; charge transfer; Dye-sensitized solar cells; Hybrid composite; hydrothermal